2015
DOI: 10.1109/jlt.2015.2414821
|View full text |Cite
|
Sign up to set email alerts
|

In-Fiber Bragg Grating Impact Force Transducer for Studying Head–Helmet Mechanical Interaction in Head Impact

Abstract: In this paper, we present the first Bragg-grating-based transducer system for application to trauma biomechanics, more specifically head-helmet contact force measurements secondary to headform impact. The transducer comprises an aluminum superstructure designed to withstand typical impact forces in helmeted impact and to have resonances that allow the overall sensor system to capture all relevant spectral components of force transients in impact. Structural finite-element models and strain-optic relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The randomized selection of data records for training and testing is vital for an accurate representation of the parent database—and all of its intrinsic characteristics— in both sets. The 7–25% split in the parent database was chosen because previous studies [ 17 , 18 , 19 ] reported that such a split is able to ensure proper training of the ML models. The data split is also useful for testing the prediction accuracy of the models in a rigorous manner.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The randomized selection of data records for training and testing is vital for an accurate representation of the parent database—and all of its intrinsic characteristics— in both sets. The 7–25% split in the parent database was chosen because previous studies [ 17 , 18 , 19 ] reported that such a split is able to ensure proper training of the ML models. The data split is also useful for testing the prediction accuracy of the models in a rigorous manner.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its unique advantages, such as light weight, small size, high flexibility, etc., the fiber optic sensor can be embedded into the helmet without influencing the functionality of the structure [ 10 , 11 ]. As one of the widely applied fiber optic sensors, the fiber Bragg grating (FBG) has attracted many interests for sensing applications such as strain [ 12 , 13 ], vibration [ 14 , 15 ], and impact [ 16 , 17 , 18 ]. Compared with other types of widely used single-point fiber optic sensors, such as fiber optic interferometers [ 19 , 20 , 21 , 22 ] and long-period fiber gratings [ 23 , 24 ], FBG has a simple and robust in-line structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrange five fit sensors on the skin of the headform, positioned on the front, back, left, right and top (Figure 2). NOTE: The sensors are a modified version of Bragg grating force transducers developed within the research group 19,20,21,22 , optimized to measure fit forces over a range of 0 to 50 N. The modified sensors have a thickness and diameter of 2.6 mm and 14 mm respectively. 2.…”
Section: Fit Force Measurementmentioning
confidence: 99%
“…Unlike conventional electrical techniques, Fibre Bragg Grating (FBG) sensors adopt light as a sensing signal, which gives FBG sensors various attractive characteristics, such as small size, light weight, immunity to electromagnetic interference, and large multiplexing capability [7,8,9]. In recent years, FBG sensors have been investigated and applied for dynamic strain measurement and modal analysis [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%